The Female Athlete Triad/Relative Energy Deficiency in Sports (RED-S) - Coelho, Alexandra Ruivo; Cardoso, Gonçalo; Brito, Marta Espanhol; Gomes, Inês Neves; Cascais, Maria João (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
In a healthy athlete, the caloric intake is sufficient for sports energy needs and body physiological functions, allowing a balance between energy availability, bone metabolism, and menstrual cycle. On the other hand, an imbalance caused by low energy availability due to a restrictive diet, eating disorders or long periods of energy expenditure leads to multisystemic deregulation favoring the essential functions of the body. This phenomenon, described as the female athlete triad, occurs in a considerable percentage of high-performance athletes, with harmful consequences for their future. The present review was carried out based on a critical analysis of the most recent publications available and aims to provide a global perception of the topic relative energy deficit in sport (RED-S). The objective is to promote the acquisition of more consolidated knowledge on an undervalued theme, enabling the acquisition of preventive strategies, early diagnosis and/or appropriate treatment.
Keywords: female athlete; low energy availability; amenorrhea; bone health; menstrual dysfunction